2018
DOI: 10.1515/jomb-2017-0047
|View full text |Cite
|
Sign up to set email alerts
|

Chemerin, Resistin, and Adiponectin in Patients with Connective Tissue Diseases

Abstract: SummaryBackgroundThe exact role of cytokines in inflammation and metabolic disorders in case of connective tissue diseases (CTDs) is under discussion.MethodsIn this study, we intended to find the relationship between the selected cytokines in inflammatory and metabolic disorders in patients with CTDs (n=55) and compared the results with those of control group subjects (n=25) matched by age and body mass. We estimated their nutritional status by the bioimpedance method. The levels of basic biochemical parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…In this study, a statistically significant increased concentration of resistin was found in patients with SSc. It complies with the elevated serum resistin level in other chronic systemic inflammatory diseases, including rheumatoid arthritis and systemic lupus erythematosus [19,20]. Taking into consideration biological profile of action, this observation suggests that increased level of resistin results in severe inflammation which seems to play one of the major roles in the pathogenesis of SSc.…”
Section: Discussionsupporting
confidence: 64%
“…In this study, a statistically significant increased concentration of resistin was found in patients with SSc. It complies with the elevated serum resistin level in other chronic systemic inflammatory diseases, including rheumatoid arthritis and systemic lupus erythematosus [19,20]. Taking into consideration biological profile of action, this observation suggests that increased level of resistin results in severe inflammation which seems to play one of the major roles in the pathogenesis of SSc.…”
Section: Discussionsupporting
confidence: 64%
“…These controversies in reported results may in part be due to the different influences of various chronic inflammatory diseases on vaspin concentrations. Thus, further studies with larger participants are needed to investigated vaspin and inflammatory cytokines associations (34, 35).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies demonstrated the close relationship between plasma vaspin levels and atherosclerosis, so, vaspin might be involved in the coronary artery disease (CAD) process (35, 36, 37). Experiments also indicated that vaspin could inhibit the release of key inflammatory markers in vascular smooth muscle cells and prevent FFA-induced apoptosis in endothelial cells, also vaspin could inhibit proliferation of vascular smooth muscle cells which induced by chemokinesis inactivation of ROS and MAPK, PI3K/Akt, and NF-kB signaling (12, 36).…”
Section: Discussionmentioning
confidence: 99%
“…Previous animal studies indicated that omentin improves endothelial functions and prevented blood pressure elevation in rats through endothelium-dependent relaxation. It has been determined that omentin increases the phosphorylation of eNOS and consequently induced relaxation in endothelium (35,39). As mentioned, obese subjects have significantly reduced omentin levels, so omentin low level may play at least in part a key role in accompanied hyper-tension in obese patients (40).…”
Section: Discussionmentioning
confidence: 97%
“…Clinical studies demonstrated the close relationship between plasma vaspin levels and atherosclerosis, so, vaspin might be involved in the coronary artery disease (CAD) process (35)(36)(37). Experiments also indicated that vaspin could inhibit the release of key inflammatory markers in vascular smooth muscle cells and prevent FFA-induced apoptosis in endothelial cells, also vaspin could inhibit proliferation of vascular smooth muscle cells which induced by chemo kinesis inactivation of ROS and MAPK, PI3K/Akt, and NF-kB signaling (12,36).…”
Section: Discussionmentioning
confidence: 99%